Political Communication Darma Wijaya in Serdang Bedagai Regional Head Election 2020 - Purba, Jaini; Samosir, Hasrat Efendi; Efendi, Erwan (Budapest International Research and Critics University, 2021)
This study aims to determine thewinner of the regional head election2020 in the Serdang Bedagai Regency by Mr. Dharma Wijaya. There are three questions, That are: First, How is Darma Wijaya's political communication in winning the regional head election of Serdang Bedagai, Second, What is the political role of Mr. Darma Wijaya towards Party and Community Leaders in Serdang Bedagai, Three What is the media of political communication of Mr. Darma Wijaya in raising votes in Serdang Begadai. Theoretical framework in this study using group communication and interpersonal communication and mass media. Model of group communication according to Michael Burgoon and Joseph A. Devito.This study uses a qualitative approach through the design of a case study model. Data collection techniques through:1. Interview 2. Observation 3. Documentation Study. Informants is taken by purposive sampling technique. The data is processed according to Sugiono, through three steps, that are Data Reduction, Data Presentation and Conclusion Drawing or Conclusion Verification. The results of the study is group communication inthe winner of the regional head election 2020 in the Serdang Bedagai Regencyby Mr. Darma Wijaya involved elements of the community through WhatsApp Groups (WAG) to socialize policies and work programs to the community.By considering every group in the community to coordinate and be responsible for the winning process, WA groups isbuild as much as possible and layered, meaning starting from the smallest level group in the village to the district level, from the many media used, the WA group seems to be the most effective in binding potential voters. Political issues and the socialization of the programs offered are well socialized, cheap and fast